Developing the National Software Market: Public Policy Alternatives - Marina Doroshenko; Kirill Skripkin (Foresight and STI Governance)
Today governments in a range of countries, including Russia, consider the promotion of open source software as an important policy tool for the development of information technologies. Since 2010 in Russia, an initiative has been undertaken to establish a National Software Platform (a set of applications based on Open Source) which, it is presumed, will be compulsorily embedded into the system of public administration. The paper assesses the efficiency of government policy in the field of Open Source and provides recommendations for its improvement.